A modified nano shell powder oil-displacing agent, preparation method and application thereof

By calcining and modifying the shell powder at high temperature, a modified nanoshell powder oil repellent was prepared, which solved the problems of low recovery rate and high nanomaterial cost in low permeability reservoirs, and achieved efficient and economical crude oil recovery effect.

CN118931518BActive Publication Date: 2025-04-22东营江源化工有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411433153.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-04-22
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve crude oil recovery in low-permeability reservoirs, and the production cost of nanomaterials is high and the dispersion stability is poor, making it difficult to apply on a large scale.

Method used

By calcining and modifying the shell powder at high temperature, a modified nano shell powder oil repellent with a particle size of 20~90nm was prepared to enhance its hydrophobicity and adsorption, reduce oil-water interface tension, and improve crude oil recovery.

Benefits of technology

It has achieved improved crude oil recovery in low-permeability reservoirs, reduced oil flooding costs, and the porous structure of nano shell powder can adsorb more surfactants and reduce adsorption losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118931518B_ABST
    Figure CN118931518B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of oilfield chemistry, specifically to a modified nano shell powder oil-displacing agent, a preparation method and application thereof, characterized in that the steps include: S1, high temperature calcination: pre-treating shells to make coarse shell powder, and calcining at high temperature under anaerobic conditions; S2, modification: ball milling the coarse shell powder after calcination in S1 to obtain nano shell powder, modifying the nano shell powder with a silane coupling agent, and post-processing after the modification to obtain the modified nano shell powder oil-displacing agent; the particle size of the nano shell powder after ball milling in S1 is 20-90nm. The present invention changes the microstructure of shell powder through high temperature calcination and modified hydrolysis, and the properties also change accordingly, and the obtained modified nano shell powder oil-displacing agent has better performance in improving crude oil recovery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, in particular to a modified nano shell powder oil displacement agent, a preparation method and application thereof. Background Art

[0002] Low permeability reservoirs have smaller pore sizes, larger specific surface areas, and stronger heterogeneity. High molecular weight polymers are difficult to inject, and the adsorption and retention losses of alkali and surfactants increase, which increases the cost of oil recovery. Therefore, it is urgent to study new oil recovery methods that can overcome the above problems. Nanofluid flooding technology has brought hope to the development of low permeability reservoirs. The size of nanoparticles is 1 to 100nm, which is smaller than the pore size of low permeability reservoirs. They can migrate smoothly in the pores of low permeability reservoirs, and the interaction between nanoscale particles and reservoir walls, water phases, and oil phases is stronger. These properties give nanofluids great development potential in the field of improving oil recovery in low permeability reservoirs.

[0003] Currently, nanomaterials used for oil recovery include metal oxides such as aluminum oxide, titanium dioxide, and copper oxide, non-metal oxides such as silicon dioxide, organic particles such as carbon nanotubes and graphene, and nanoparticles such as polymer microspheres. However, they generally have defects such as multiple preparation methods, complex processes, high production costs, poor dispersion stability, and poor recovery enhancement effects. They are difficult to apply on a large scale in mines and have limited application effects. Therefore, reducing the production cost of nanoparticles and developing cheap and environmentally friendly nanomaterials is one of the goals to be overcome in the future.

[0004] 90% of the shells are CaCO3, 1% to 5% are organic matrices, and present a "brick and mud" structure that cannot be synthesized by humans, in which CaCO3 mainly exists in the crystal form of aragonite and calcite. Therefore, shells are a low-cost source of CaCO3, and by further processing them, there is an opportunity to obtain other more valuable materials or preparations. At the same time, shell porous materials show excellent adsorption, dispersion, porosity and non-toxicity. Therefore, attempts can be made to crush discarded shells into nanoparticles for research, but the surface of natural shells has a large number of hydroxyl groups and is highly hydrophilic, and better performance needs to be obtained through surface modification, such as stronger dispersibility and stability in the aqueous phase, and a stronger ability to reduce the oil-water interfacial tension (IFT) and improve the wettability of the reservoir wall.

[0005] However, there is no case in the prior art of using nano shell powder in the field of crude oil extraction to improve crude oil recovery. Therefore, it is necessary to develop a modified nano shell powder that can be used to improve crude oil recovery, while solving the problem of lack of cheap and environmentally friendly nano materials and waste of shell resources in the field of crude oil extraction. Summary of the invention

[0006] The present invention is made to solve the above-mentioned problems, and aims to provide a modified nano shell powder oil-displacing agent that can improve the recovery rate of low-permeability oil reservoirs, and its preparation method and application, so as to solve the above-mentioned technical problems.

[0007] The first aspect of the present invention provides a method for preparing a modified nano shell powder oil-displacing agent, characterized in that it comprises the following steps:

[0008] S1. Calcination: pre-treating the shells to obtain shell powder, and calcining the shell powder under anaerobic conditions at a temperature of 900-1000°C;

[0009] S2, modification: ball-milling the calcined shell powder in S1 to obtain nano shell powder, modifying the nano shell powder with a silane coupling agent, and performing post-processing to obtain the modified nano shell powder oil-displacing agent;

[0010] The particle size of the nano shell powder after ball milling in S1 is 20-90 nm.

[0011] After research, it was found that compared with other inorganic nanomaterials, the loose porous structure of nano shell powder makes it have a lower density, and low density can reduce the sedimentation of particles, but the surface of nano shell powder has more hydroxyl groups and has strong hydrophilicity. At the same time, the porous nano shell powder particles have a larger specific surface area, stronger adsorption, and more active sites. Therefore, the present invention performs surface modification on nano shell powder, and enhances its hydrophobicity by grafting organic groups, which is beneficial to further reduce the oil-water interfacial tension and further improve the crude oil recovery rate.

[0012] Furthermore, in order to improve the performance of shell powder, the present invention calcines the shell powder at high temperature to gradually decompose CaCO3 and some trace organic matter in the shell powder. Gas is generated during the decomposition process, making the surface of the shell powder loose and porous. The porous structure of nano shell powder can absorb more surfactants, thereby reducing the adsorption loss of surfactants in the formation.

[0013] At the same time, high-temperature calcination can decompose CaCO3 in shell powder to form active calcium oxide. When modified nano shell powder is used for oil recovery, the active calcium oxide on the modified nano shell powder will generate calcium hydroxide when it meets water, making the solution alkaline. The alkali can react with the petroleum acid in the crude oil to produce surfactants, which further assists in reducing the oil-water interfacial tension, changing the rock wettability from oil-wet to water-wet, and promoting the formation of crude oil emulsion.

[0014] The invention obtains a modified nano shell powder oil-displacing agent by calcining and modifying common nano shell powder at high temperature, and realizes the integration of multiple functions on the modified nano shell powder oil-displacing agent.

[0015] The study found that the particle size of nano-shell powder affects its permeability in rock pores. Nano-shell powder with smaller particle sizes can more easily enter the tiny pores of rocks and more easily form a stable emulsification effect at the oil-water interface, thereby improving oil recovery efficiency. On the contrary, nano-shell powder with larger particle sizes may not be able to enter certain pores, resulting in limited oil recovery effects. At the same time, in porous media, nano-shell powder with larger particle sizes may be screened at smaller pores, resulting in uneven distribution in the formation.

[0016] However, when the nanoshell powder is too small, less than 20nm, although it is easier for the nanoshell powder to enter the rock pores, the strong Brownian motion may cause it to be unevenly distributed in the pores and easily agglomerated. When the nanoshell powder is larger than 90nm, these nanoshell powders may have more advantages in fluidity control, but the permeability is poor and may not be able to enter all pores.

[0017] Therefore, the particle size of the nano shell powder is controlled to be 20-90 nm in the present invention. The nano shell powder in this range not only has good permeability, but is also easier to maintain stable dispersion, has good stability, and is suitable for oil displacement.

[0018] In some embodiments of the present invention, in S1, the calcination time is 4 to 5 hours.

[0019] When the calcination temperature reaches 900℃ and above, part of the biological calcium carbonate in the shell powder is converted into CaO, so that when the shell powder is dissolved in the solution, the pH of the solution increases from 7 to 9~10, which can play the role of alkali drive during oil displacement and enhance the effect of improving oil recovery; and the CaCO3 crystal form of the shell powder changes to form a large number of pore diameters with a large specific surface area, which helps to enhance the dispersion of nano shell powder in water and better surface modification active sites. The hydrophobically modified nano shell powder particles can reduce the oil-water interfacial tension and have a better in-situ emulsification effect with crude oil, so they show a better effect of improving oil recovery.

[0020] Furthermore, the present invention controls the amount of active calcium oxide generated by controlling the temperature and time of high-temperature calcination, thereby preventing the modified nano-shell powder oil-displacing agent from having too little active calcium oxide, resulting in poor effect of assisting in reducing oil-water interfacial tension, and preventing the modified nano-shell powder from having too much active calcium oxide, resulting in excessive calcium hydroxide generated when the modified nano-shell powder oil-displacing agent is used, resulting in precipitation or precipitation, and affecting the crude oil recovery rate.

[0021] In some embodiments of the present invention, S2 specifically includes: ball milling the calcined shell powder in S1 to obtain nano shell powder, mixing the nano shell powder with a dispersant and ultrasonically dispersing it evenly to obtain a nano shell powder dispersion, adjusting the pH of the nano shell powder dispersion and adding a silane coupling agent hydrolyzate and stirring for hydrolysis, condensing and refluxing the reaction, and after the reaction is completed, post-treating the reaction solution to obtain the modified nano shell powder oil displacement agent.

[0022] In some embodiments of the present invention, the step of preparing the silane coupling agent hydrolyzate includes: adding the silane coupling agent to an ethanol aqueous solution and stirring and hydrolyzing to obtain the silane coupling agent hydrolyzate.

[0023] In some embodiments of the present invention, the mass fraction of the silane coupling agent in the silane coupling agent hydrolyzate is 7.3-10 wt %.

[0024] In some embodiments of the present invention, the pretreatment in S1 specifically includes: soaking the shells in an acidic solution for 10 to 24 hours, and after soaking, washing the shells to neutrality and then drying them.

[0025] Shells need to be soaked and cleaned before grinding to reduce the introduction of impurities into shell powder.

[0026] In some embodiments of the present invention, the pH of the nano shell powder dispersion in S2 is adjusted to 9-10.

[0027] In some embodiments of the present invention, the liquid-to-solid ratio of the nano-shell powder to the dispersant is 1: (30-40) mL / g, and the dispersant is anhydrous ethanol.

[0028] The second aspect of the present invention is a modified nano-shell powder oil-displacing agent, characterized in that the modified nano-shell powder oil-displacing agent is prepared according to the preparation method described in any one of the first aspects.

[0029] The third aspect of the present invention is an application of the modified nano shell powder oil-displacing agent as described in the second aspect, characterized in that the modified nano shell powder oil-displacing agent is used in the field of crude oil extraction.

[0030] By implementing the above technical solution, the present invention has the following beneficial effects:

[0031] 1. The present invention changes the microstructure of shell powder through high-temperature calcination and modified hydrolysis, and the properties are also changed accordingly. The obtained modified nano shell powder oil-displacing agent has better performance in improving crude oil recovery.

[0032] 2. The present invention performs surface modification on nano shell powder and enhances its hydrophobicity by grafting organic groups, which is beneficial to further reduce the oil-water interfacial tension and further improve the crude oil recovery rate.

[0033] 3. In order to improve the performance of shell powder, the present invention calcines the shell powder at high temperature to gradually decompose CaCO3 and some trace organic matter in the shell powder. A large amount of energy is generated during the decomposition process, making the surface of the shell powder loose and porous. The porous structure of the nano shell powder oil displacement agent finally obtained can absorb more surfactants, thereby reducing the adsorption loss of surfactants in the formation. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The morphological structure diagram of the modified nano shell powder prepared in Example 1 of the present invention is obtained by scanning electron microscopy;

[0035] Figure 2 The particle size distribution diagram of the dispersion system formed by the modified nano shell powder and water prepared in Example 1;

[0036] Figure 3 The Fourier transform infrared spectra of the modified nano shell powder and the unmodified nano shell powder prepared in Example 1;

[0037] Figure 4 The contact angle diagram of the unmodified nano shell powder and the contact angle diagram of the modified nano shell powder prepared in Example 1;

[0038] Figure 5 This is a comparison chart of the emulsification effects of the AOS solution and the modified nano-shell powder-AOS dispersion system in the oil displacement experiment of Example 1. DETAILED DESCRIPTION

[0039] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below in conjunction with embodiments and drawings.

[0040] Example 1: Preparation and performance testing of modified nano shell powder

[0041] S1, high temperature calcination: weigh 10g of scallop shells and soak them in 1%wt HCl solution for 24h, then wash them with distilled water until neutral and dry them; coarsely grind the scallop shells and pass them through a 150-mesh sieve to obtain shell powder; isolate the scallop shell powder from oxygen and calcine it at high temperature at 900°C for 3h;

[0042] S2. Modification: The calcined scallop shell powder was ball-milled at 600-800 r / min for 6 hours to form particles with a particle size of about 20 nm. Determination of the average particle size of shell powder: The average particle size of shell powder was measured by a laser nanoparticle size analyzer, and the test was performed three times to obtain the average particle size.

[0043] The nano-shell powder obtained by ball milling was mixed with anhydrous ethanol at a liquid-to-solid ratio of 1:30 mL / g, and ultrasonically dispersed for 30 minutes to uniformly disperse the nano-shell powder in the anhydrous ethanol to obtain a nano-shell powder dispersion.

[0044] 7.3g of silane coupling agent KH570 was added to ethanol aqueous solution (ethanol to water volume ratio of 4:1) to prepare a 7.3wt% solution and stirred and hydrolyzed with a magnetic stirrer for 1 hour to obtain a silane coupling agent hydrolyzate. The nano shell powder dispersion was transferred to a three-necked flask, and an appropriate amount of NaOH was added to adjust the solution pH to 9. In a constant temperature magnetic stirrer, the silane coupling agent hydrolyzate was slowly added dropwise at 70°C and stirred, and condensed and refluxed for 4 hours; after the reaction was completed, the reaction solution was repeatedly washed with anhydrous ethanol and filtered until the filtrate was clear and transparent, and the filter cake was placed in a vacuum drying oven and dried at 70°C for 12 hours to obtain modified nano shell powder particles, which were then ground into powder to obtain a modified nano shell powder oil displacement agent.

[0045] The modified nano shell powder oil displacement agent obtained in the example was observed by scanning electron microscopy. Figure 1 As shown, it can be seen that the obtained modified nano shell powder particles are nanometer-level, and a certain amount of organic groups are grafted on the surface, which effectively reduces the hydrophilicity of the modified nano shell powder oil-displacing agent.

[0046] Furthermore, the modified nano shell powder oil displacement agent prepared above was subjected to an oil displacement experiment, and the detection steps were as follows:

[0047] (1) Weigh 4 g of activated nano-shell powder with a particle size of 20 nm, add it to 200 ml of deionized water to prepare a 0.2 wt% AOS (α-olefin sulfonate) solution, stir it thoroughly, and disperse it by ultrasonic for 15 minutes to obtain a modified nano-shell powder-AOS dispersion. The particle size distribution of the dispersion system measured by the laser nanoparticle size analyzer is shown in the figure below: Figure 2 shown.

[0048] (2) A core with a certain permeability is saturated with deionized water by vacuum pumping, and then the core is saturated with oil until no water comes out. The original oil saturation of the rock in the core is calculated. The core is flooded with water until no oil comes out. The water flooding recovery factor is calculated. Then, the nano-shell powder-AOS dispersion is injected into the artificial core after water flooding to conduct an oil flooding experiment, calculate the recovery factor, and calculate the value of the enhanced recovery factor.

[0049] Experimental results: Figure 1 As shown in the figure, the modified nano shell powder obtained is spherical particles, and the particle size of the modified nano scallop powder (7.3% KH570)-AOS (0.2wt%) dispersion system is mainly concentrated at 85nm, the pH value is 10, and the oil-water interfacial tension is 1.2×10 -3mN / m, while the oil-water interfacial tension of 0.2wt% AOS is 4.0×10 -3 mN / m, and a 40md core was used for oil displacement experiments, with a recovery rate of 43.1%. The same concentration of AOS solution was used to carry out oil displacement experiments on a 40md core, with a recovery rate of 36.3%.

[0050] In the embodiment, the modified nano shell powder and the unmodified nano shell powder are detected respectively, and the infrared spectra of the modified nano shell powder and the unmodified shell powder are as follows: Figure 3 As shown in the figure, the spectrum of modified nano shell powder shows characteristic peaks of the modifier. -1 It is due to the asymmetric and symmetric stretching vibration of the CH bond in the -CH3 group. 1718.21cm -1 The peak at 1458.18cm-1 is the C=O stretching vibration peak. The peak at 1458.18cm-1 is the CH bond vibration absorption peak. This indicates that the surface of the nano shell powder has been successfully grafted with -CH3 groups and the modification has been successful.

[0051] The contact angles of nano shell powder before and after modification are as follows: Figure 4 As shown; Figure 4 (a) is the unmodified nano shell powder, and its contact angle is 12.4°. Figure 4 (b) is the modified nano shell powder, and its contact angle is 80.4°, which changes from strong hydrophilicity to weak hydrophilicity. The emulsification effect of the modified nano shell powder oil displacement agent is shown in Figure 5 As shown, Figure 5 (a) is the unmodified nano shell powder-AOS dispersion system. Figure 5 (b) in the figure is a modified nano-shell powder-AOS dispersion system. Compared with the unmodified nano-shell powder, the modified nano-shell powder oil displacement agent has a better oil-water mixing effect in the produced fluid during the oil displacement process, that is, a better emulsification effect.

[0052] Example 2: Particle size screening of nano shell powder

[0053] In this embodiment, modified nano shell powder was prepared according to the steps in Example 1 (calcination temperature was 900° C., calcination was performed for 4 h, and the modified nano shell powder was ground into nano particles of different sizes using a ball mill, modified using a modifier with a concentration of 7.3 wt%, and an oil displacement experiment was performed using a 40 mD artificial core, and the water flooding recovery rate was 56.7%). The grinding particle size of the nano shell powder was further screened, and the performance of the modified nano shell powder oil displacement agent was tested. The test results are as follows:

[0054] Table 1 Particle size screening test results

[0055] Serial number Particle size of nano shell powder (nm) Recovery rate 1 10 39.1% 2 20 45.9% 3 50 45.1% 4 90 42.9% 5 110 38.2% 6 130 37.1%

[0056] According to the experimental results, when the particle size of nano shell powder is 20~90nm, the water drive recovery rate is significantly improved. Therefore, the modified nano shell powder oil displacement agent made from nano shell powder in this range has better permeability, is easier to maintain stable dispersion, has better stability, and is suitable for oil recovery.

[0057] Example 3: High temperature calcination conditions screening

[0058] In this embodiment, modified nano shell powder was prepared according to the steps in Example 1, ground into 85 nm nanoparticles by a ball mill, modified by a modifier with a concentration of 7.3 wt%, and an oil displacement experiment was carried out in a 40 mD artificial core. The water flooding recovery rate was 56.7%. The high-temperature calcination conditions were further screened, and the performance of the modified nano shell powder was tested. The test results are as follows:

[0059] Table 2 High temperature calcination conditions screening results

[0060] Serial number High temperature calcination temperature (℃) High temperature calcination time (h) Recovery rate 1 800 3 37.2% 2 850 3 37.8% 3 900 4 42.9% 4 950 4 43.2% 5 1000 4 42.7% 6 900 5 42.1% 7 900 7 41.1%

[0061] According to the experimental results, when the high-temperature calcination temperature is 900~1000℃ and the high-temperature calcination time is 4~5 hours, the water flooding recovery rate of the modified nano-shell powder oil-displacing agent is higher.

[0062] Example 4: Screening of modified hydrolysis conditions

[0063] In this embodiment, the modified nano shell powder oil-displacing agent is prepared according to the steps in embodiment 1, the calcination temperature is 900°C, the calcination is 4h, and the nano particles of 85nm are ground into nano particles by a ball mill. The modified particles are modified by modifiers of different concentrations, and the oil displacement experiment is carried out in a 40mD artificial core. The water flooding recovery rate is 56.7%. The modification conditions are further screened, and the performance of the modified nano shell powder oil-displacing agent is tested. The test results are as follows:

[0064] Table 3 Results of screening of modified hydrolysis conditions

[0065] Serial number pH of nano shell powder dispersion Liquid-to-solid ratio of nano shell powder to dispersant (mL / g) Mass fraction of silane coupling agent (wt%) Contact angle Recovery rate 1 9 1:30 7.3 80.4° 43.1% 2 10 1:40 8 80.3° 43.3% 3 9 1:30 10 80.2° 42.8% 4 9 1:30 5 40.7° 39.9%

[0066] According to the experimental results, when the mass fraction of silane coupling agent in the silane coupling agent hydrolyzate is 7.3~10wt%, the contact angle of the modified nano-shell powder is greater than 80°, which changes the modified nano-shell powder from strongly hydrophilic to weakly hydrophilic, so that the modified nano-shell powder oil-displacing agent prepared therefrom has better oil-water mixing effect in the produced fluid during the oil displacement process and higher water drive recovery rate.

[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a modified nano shell powder oil-displacing agent, characterized in that: The following steps are involved: S1, calcination: pre-treating the shells to make shell powder, and calcining under anaerobic conditions, the calcination temperature is 900-1000°C, and the calcination time is 4-5 hours; The pretreatment in S1 specifically includes: soaking the shells in an acidic solution for 10 to 24 hours, washing the shells to neutrality and then drying them after soaking; S2, modification: ball-milling the calcined shell powder in S1 to obtain nano shell powder, wherein the particle size of the nano shell powder is 20-90 nm, mixing the nano shell powder with a dispersant and uniformly dispersing by ultrasonication to obtain a nano shell powder dispersion, adjusting the pH of the nano shell powder dispersion to 9-10, adding a silane coupling agent hydrolyzate and stirring for hydrolysis, condensing and refluxing to react, and after the reaction is completed, post-treating the reaction solution to obtain the modified nano shell powder oil-displacing agent; the dispersant is anhydrous ethanol.

2. The preparation method according to claim 1, characterized in that: The preparation steps of the silane coupling agent hydrolyzate include: adding the silane coupling agent into the ethanol aqueous solution and stirring and hydrolyzing to obtain the silane coupling agent hydrolyzate.

3. The preparation method according to claim 2, characterized in that: The mass fraction of the silane coupling agent in the silane coupling agent hydrolyzate is 7.3-10wt%.

4. The preparation method according to claim 3, characterized in that: The solid-liquid ratio of the nano shell powder to the dispersant is 1 g: (30-40) mL.

5. A modified nano shell powder oil-displacing agent, characterized in that: The modified nano shell powder oil-displacing agent is prepared according to the preparation method according to any one of claims 1 to 4.

6. An application of the modified nano shell powder oil-displacing agent as claimed in claim 5, characterized in that: The modified nano shell powder oil-displacing agent is used in the field of crude oil exploitation.

Citation Information

Patent Citations

  • Composite comprising well treatment agent and / or a tracer adhered onto a calcined substrate of a metal oxide coated core and a method of using the same

    CA2955926A1

  • Calcined shell micropore structure-based sea surface oil stain treatment micropowder preparation method

    CN105837776A